Norwegian scabies mimicking rupioid psoriasis Sarna norueguesa mimetizando psoríase rupioide - Juliana Bastos Costa; Virna Lygia Lobo Rocha de Sousa; Pedro Bezerra da Trindade Neto; Thomás de Aquino Paulo Filho; Virgínia Célia Dias Florêncio Cabral; Patrícia Moura Rossiter Pinheiro (Sociedade Brasileira de Dermatologia, 2012)
Norwegian scabies is a highly contagious skin infestation caused by an ectoparasite, Scarcoptes scabiei var. Hominis, which mainly affects immunosuppressed individuals. Clinically, it may simulate various dermatoses such as psoriasis, Darier's disease, seborrheic dermatitis, among others. This is a case report of a 33-year-old woman, immunocompetent, diagnosed with generalized anxiety disorder (cancer phobia), who had erythematous, well-defined plaques, covered with rupioid crusts, on her neck, axillary folds, breast, periumbilical region, groin area, besides upper back and elbows, mimicking an extremely rare variant of psoriasis, denominated rupioid psoriasis. A sarna norueguesa é uma infestação cutânea altamente contagiosa causada pelo ectoparasita Sarcoptes scabiei var. hominis, que atinge principalmente indivíduos imunossuprimidos. Clinicamente, pode simular várias dermatoses, tais como psoríase, doença de Darier, dermatite seborréica, entre outras. O artigo relata o caso de uma mulher de 33 anos, imunocompetente, porém com diagnóstico de transtorno de ansiedade generalizada e cancerofobia, que apresentava placas bem delimitadas, sobre base eritematosa, recobertas por crostas rupioides, nas regiões cervical, axilar, mamária, umbilical, inguinal, além de dorso superior e cotovelos, mimetizando uma variante extremamente rara de psoríase, denominada psoríase rupioide.